Self-Leadership Among Healthcare Workers: A Mediator for the Effects of Job Autonomy on Work Engagement and Health - van Dorssen-Boog, Pauline; de Jong, Jeroen; Veld, Monique; Van Vuuren, Tinka (Frontiers in Psychology, 2020)
Due to the high workload, working within the healthcare industry can be quite demanding. This often results in high rates of absenteeism, unfulfilled vacancies and voluntary turnover among healthcare workers. We expect that job autonomy is an important resource for work engagement and health of healthcare workers since it satisfies the basic need for autonomy. However, we propose that this relationship between job autonomy and work engagement and health can be explained by self-leadership. Self-leading individuals take initiative and responsibility and are assumed to use self-influencing strategies (e.g. goal-setting, self-observation, creating natural rewards) as a way to improve motivation and general well-being. Employees from two healthcare organisations (N=224 and N=113) completed a questionnaire containing measures of job autonomy, work engagement, general health and self-leadership. The hypothesized model was tested using a series of regressions, and the results confirmed the indirect relationships between job autonomy and work engagement and general health respectively through natural rewards strategies. The behavior-focused and cognitive self-leadership strategies were as mediator marginally significant: positively for work engagement and negatively for general health. Self-leadership behavior was not related with work engagement and general health. Implications of the findings for theory and practice on healthy healthcare workers are discussed. Keywords: Job autonomy, Self-leadership, Work Engagement , Health, Healthcare workers